Uptake Potential of Some Heavy Metals by Vetiver Grass - Roongtanakiat, Nualchavee; Chairoj, Prapai (Agriculture and Natural Resources, 2001)
The uptake potential of upland vetiver grass (Vetiveria nemoralis) ecotype Kamphaeng Phet and lowland vetiver grass (Vetiveria zizanioides) ecotypes Ratchaburi and Surat Thani, for different heavy metals was evaluated. Varying amounts of manganese (Mn), zinc (Zn), copper (Cu) cadmium (Cd) and lead (Pb) were applied to one-month old vetiver grass planted in pots. Vetiver grass plants were harvested at 60 and 120 days after the heavy metal application and the concentrations of the heavy metals in shoot and root parts were determined using atomic absorption spectrophotometry. The results indicated that at the concentrations tested, the heavy metals applied had no significant effect on growth of all vetiver grass ecotypes. Vetiver grass harvested at 120 days yielded more shoot dry matter than those harvested at 60 days. The Ratchaburi ecotype demonstrated significantly increased in root mass at the 120-day harvest. No obvious increase for Kamphaeng Phet and Surat Thani and no significant difference in root between these ecotypes mass were observed. For the three vetiver grass ecotypes tested, the uptake of heavy metals was proportional to the concentration of the applied heavy metals. The Ratchaburi ecotype had the highest concentration of the heavy metals in shoots, except at the 120-day harvest, Pb concentration was significantly lower than that of the Kamphaeng Phet ecotype. The concentration of heavy metals in vetiver grass shoots harvested at 120 days was lower than that of the 60-day harvest due to dilution effects. However, heavy metal concentration in roots was increased from 60- to 120- day harvest. This may be due to the spatial limitations of the pot or the restricted translocation of heavy metals from roots to shoots which resulted in an accumulation of the heavy metals in the roots. Therefore, when utilizing vetiver grass for the phytoremediation of heavy metal contaminated soil, the above ground biomass should be regularly cut to stimulate regrowth and the translocation of heavy metals to shoots.